2012
DOI: 10.1002/lsm.21156
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of melasma using a combination of microdermabrasion and Q‐switched Nd:YAG lasers

Abstract: Microdermabrasion plus low-fluence QS Nd:YAG laser treatment is a simple, non-invasive procedure with minimal risk, no recovery time, and long-lasting remission. Treatment works on all skin phototypes in just two to three treatment sessions. Subject compliance with skin care was excellent, probably due to the dramatic improvement observed within 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 44 publications
6
51
1
2
Order By: Relevance
“…Similarly, microdermabrasion has also been shown to have synergistic effects when used along with Q switched Nd: YAG laser, glycolic acid and topical retinoids. 9,10,11 Despite these studies based on similar principles, we could not find any study which evaluated the synergistic effects of kojic acid and microdermabrasion as compared to kojic acid alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, microdermabrasion has also been shown to have synergistic effects when used along with Q switched Nd: YAG laser, glycolic acid and topical retinoids. 9,10,11 Despite these studies based on similar principles, we could not find any study which evaluated the synergistic effects of kojic acid and microdermabrasion as compared to kojic acid alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the synergistic effects of microdermabrasion in combination with other therapies such as Q switched Nd:YAG laser and glycolic acid and retinoic acid chemical peels have been reported. 9,10,11 Skin preferentially allows low molecular weight, lipophilic molecules, to penetrate intact skin as compared to hydrophilic molecules and macromolecules. 12 The hydrophilic nature of kojic acid limits its ability to penetrate through the stratum corneum, thereby hindering the delivery of the drug to melanocytes which are localized to the basal layer.…”
Section: Introductionmentioning
confidence: 99%
“…These short pulse targets the small chromophore of melanin and generates photoacoustic effect that leads to melanin destruction [11][12][13][14][15][16] . The threshold for the photoacoustic damage of skin by Q-switched Nd:YAG laser (QSNY) light is between 1.6-5 J/cm 2 , which indicates that pigment destruction can occur without skin ablation.…”
Section: Q-switched Lasersmentioning
confidence: 99%
“…Several studies reported good improvement of melasma [68][69][70][71], especially when patients were pretreated with TCC [72] or when combined with glycolic acid peels [73], IPL [74] or dermabrasion [75]. However, reports of patients developing spotty hypopigmentation, depigmentation, leukotrichia, rebound hyperpigmentation and recurrence of melasma are noteworthy especially with too frequent (weekly) and too many sessions (>6-10) [71,76,77].…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%
“…Different topical therapy combinations have been studied and combining topical, oral therapies with each other and/or with peeling and light therapies add to the efficacy of treatment especially in recalcitrant cases. Starting by TCC before other treatment modalities decrease the incidence of PIH and may decrease melasma relapse [54,61,72,74,75,79,83,89,99].…”
Section: Combination Therapymentioning
confidence: 99%